Kemijska reakcijska tehnika I: Navodila za opravljanje laboratorijskih vaj - Pečar, Darja (University of Maribor Press, 2025)
Chemical Reaction Engineering I: Manual for Performing Laboratory Exercises. Manual for performing laboratory exercises in the course Chemical Reaction Engineering I represents a teaching aid for students to be able to approach experimental work in the laboratory.